Effectiveness of Antibiotic Use in the Prevention and Treatment of Respiratory Tract Infections - Andika Alfiansyah; Fadli Fadli; Lutvi Anggraeni; Khrisna Agung Cendekiawan (Journal of Pharmacopoeia, 2025)
This study aims to analyze the effectiveness of the use of antibiotics in the prevention and treatment of respiratory tract infections. This study uses the Systematic Literature Review (SLR) method. There are three stages carried out in mapping the effectiveness of antibiotic use in the prevention and treatment of respiratory tract infections, namely: 1) harvesting data, 2) screening data, and 3) Data Analysis and Visualization. This study uses a database from Scopus with scientific journals as many as 9 articles from the range of 2021 to 2024. The effectiveness of antibiotic use in the prevention and treatment of respiratory tract infections is influenced by a variety of factors, including patient adherence, duration of therapy, and vaccine availability and use. Excessive or improper use of antibiotics can increase bacterial resistance, so more sustainable strategies, such as vaccination and stricter antibiotic use policies, are needed to improve the effectiveness of prevention and treatment of respiratory tract infections. The implications of this study are expected to be useful for future researchers and can be used in clinical applications